Ligand-specific activation trajectories dictate GPCR signalling in cells - Romy Thomas; Pauline S. Jacoby; Chiara De Faveri; Cécile Derieux; Aenne-Dorothea Liebing; Barbora Melkes; Hans-Joachim Martini; Marcel Bermúdez; Claudia Stäubert; Martin J. Lohse; Irene Coin; Andreas Bock (Nature, 2026)
Abstract G-protein-coupled receptors (GPCRs) are key mediators of cell communication and represent the most important class of drug targets 1,2 . Biophysical studies with purified GPCRs in vitro have suggested that they exist in an equilibrium of distinct inactive and active states, which is modulated by ligands in an efficacy-dependent manner 3–11 . However, how efficacy is encoded and whether multiple receptor states occur in living cells remain unclear. Here we use genetic code expansion 12 and bioorthogonal labelling 13–16 to generate a panel of fluorescence-based biosensors for a prototypical GPCR, the M 2 muscarinic acetylcholine receptor (M 2 R). These biosensors enable real-time monitoring of agonist-promoted conformational changes across the receptor’s extracellular surface in intact cells. We demonstrate that different agonists produce equilibria of at least four distinct active states of the G-protein-bound M 2 R, each with a different ability to activate G proteins. The formation of these M 2 R–G-protein complexes occurs over 0.2–5 s along trajectories that involve both common and ligand-specific conformational changes and appear to determine G-protein selectivity. These observations reveal the molecular nature of ligand efficacy in intact cells. Selectively exploiting such different GPCR activation trajectories and conformational equilibria may open new avenues for GPCR drug discovery.